Hydroxycinnamic acid derivatives effect on hypercholesterolemia, comparison with ezetimibe: Permeability assays and FTIR spectroscopy on Caco-2 ​cell line - Asma Ressaissi; Maria Luísa M. Serralheiro (Elsevier, 2022)
High blood cholesterol levels may increase the risk of developing atherosclerosis. Since intestinal cholesterol absorption plays a major role in maintaining total body cholesterol homeostasis, the aim of the present study was to compare the effect of ezetimibe and three hydroxycinnamic acid derivatives (rosmarinic acid, chlorogenic acid and m-coumaric acid) that are present in several medicinal plants on cholesterol absorption in the intestinal Caco-2 ​cells. In addition to the permeability assays, studies on alteration of the biochemical properties of Caco-2 ​cells under the effect of ezetimibe and hydroxycinnamic acid derivatives was evaluated using FTIR accompanied with multivariate analysis by PCA. The cholesterol permeability assays showed that these compounds could decrease cholesterol permeability with a percentage ranging from 76.98 to 96.6% with the highest inhibition for ezetimibe. whereas the FTIR studies didn't show similar changes between ezetimibe and the three hydroxycinnamic acid derivatives in protein and nucleic acids region, suggesting that these compounds have hypocholesterolemic effect. Nevertheless, each compound originated a different change on Caco-2 treated cells suggesting a different mode of action.